"Pollution prevention" is the key to drive sustainability: Preliminary findings from a tannery unit in India. Issue 3 (9th April 2018) - Kumar Gupta, Sandeep; Gupta, Sanjeev; Gayathiri, S.
Abstract : Purpose: The purpose of this paper is to demonstrate the difference in firm performance between pollution prevention and pollution control strategies using a selected case study from the Indian leather industry. Design/methodology/approach: This study followed a case study-based inductive research approach to validate the proposed preposition on field. The case-study analysis was based on qualitative and quantitative data. The authors developed a questionnaire and an interview protocol to capture the data about different industrial practices and motivation behind them. The study followed the concept of the triple bottom line approach for assessing the progress of the case firm on sustainability scale. Findings: With the help of pollution preventive measures, such as replacement of salted skin with fresh skin and chromium salt with a phosphonium-based tanning agent, the case firm could overcome the biggest challenge of bringing down the level of total dissolved solid from 40, 000 to 5, 000 ppm in the raw effluent. Moreover, the firm has successfully recycled and converted tannery scraps and other waste into organic manure for internal use in its own plantations. Research limitations/implications: The findings of this study could not be generalized as these are based on a single case study. Originality/value: This study presents an example of sustainable practices and their benefits to the Indian leather industry to follow.